Rubens and the human body - Wyhe, Cordula van; Wyhe, Cordula van; Rubens, Peter Paul; Rubens, Peter Paul (The body in art, 2018)
This book is the first comprehensive investigation of the most paradigmatic aspect of Baroque visual culture: the Rubensian nude. Did contemporary audiences recognise the sensuously painted 'Rubensian body' as a particular, if not peculiar, artistic repertoire? How can we best understand seventeenth-century practises of reading and viewing the Rubensian body? Can our criteria for eroticism be linked with that of Rubens? Was the body a 'fluid' category for Rubens and where does the boundary of the human body lie? It is hoped that these investigative questions will lead to a detailed evaluation about the paradigmatic status of the Rubensian body and whether we are justified in stressing its singularity within seventeenth-century Flemish and the broader early modern European visual culture